Poetica del Risveglio e Materialismo Antropologico nei Passages di Benjamin (Altre Modernità, 2019)
The present study aims to show how Benjamin’s concept of an Anthropological Materialism actually joints many sections of the  Arcades-Project together; in this work Benjamin wants to show how myth and modern rationality, but also myth and modern industrial  method of production are very closely interlaced. Refusing the bourgeois idea of progress Benjamin thinks that the „passage“ from  an historical period to the subsequent, but also the passage from a generation to the next actually occurs as a reversal gesture, thus  making the interior side, that’s to say the dreams and unconscious wishes of the past generation become the conscious contents of the awaken life of the next one.